2003
DOI: 10.1093/ajcn/78.2.250
|View full text |Cite|
|
Sign up to set email alerts
|

Essential amino acids are primarily responsible for the amino acid stimulation of muscle protein anabolism in healthy elderly adults

Abstract: Essential amino acids are primarily responsible for the amino acid-induced stimulation of muscle protein anabolism in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
481
4
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 718 publications
(525 citation statements)
references
References 32 publications
9
481
4
11
Order By: Relevance
“…immediately after absorption) [34,36], this does not appear to influence the systemic amino acid concentration, which normally increases in the elderly as well as in the young, and consequently the muscle anabolic effect of amino acids [34]. EAAs, in particular, are able to stimulate muscle protein synthesis in the elderly, whereas non-EAAs do not appear to provide any additional benefit with regard to muscle protein deposition and anabolism [35]. Among the EAAs, the branched-chain amino acid (BCAA) leucine has been shown to be a key regulator of muscle protein synthesis in both humans and rats [37][38][39].…”
Section: Amino Acids and Regulation Of Muscle Metabolism In Healthy Amentioning
confidence: 99%
See 1 more Smart Citation
“…immediately after absorption) [34,36], this does not appear to influence the systemic amino acid concentration, which normally increases in the elderly as well as in the young, and consequently the muscle anabolic effect of amino acids [34]. EAAs, in particular, are able to stimulate muscle protein synthesis in the elderly, whereas non-EAAs do not appear to provide any additional benefit with regard to muscle protein deposition and anabolism [35]. Among the EAAs, the branched-chain amino acid (BCAA) leucine has been shown to be a key regulator of muscle protein synthesis in both humans and rats [37][38][39].…”
Section: Amino Acids and Regulation Of Muscle Metabolism In Healthy Amentioning
confidence: 99%
“…A number of studies have shown that pure amino acids can stimulate muscle protein synthesis and improve net protein balance in older as well as in younger individuals [19,[32][33][34][35]. Although older persons have an increased splanchnic extraction of orally administered amino acids at first pass (i.e.…”
Section: Amino Acids and Regulation Of Muscle Metabolism In Healthy Amentioning
confidence: 99%
“…In contrast, DR has only one principal negative effect: muscle weakness due to protein wasting (Lopes, Russell, Whitwell, & Jeejeebhoy, 1982; Thomas, 2007), which also represents a health problem in both elderly subjects and patients with kidney disease (Goodpaster et al., 2006; Workeneh & Mitch, 2010). Recently, a beneficial effect of dietary protein or amino acid supplementation on muscle weakness has been proposed (Paddon‐Jones & Rasmussen, 2009; Paddon‐Jones, Short, Campbell, Volpi, & Wolfe, 2008; Volpi, Kobayashi, Sheffield‐Moore, Mittendorfer, & Wolfe, 2003). However, there has been concern that such a supplement may adversely affect the progression of CKD and reduce DR‐induced health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…mTORC1 signaling has consistently shown to be activated in response to both muscle loading (e.g., resistance exercise), and amino acid consumption/treatment (Marcotte, West, & Baar, 2015), and as such these stimuli represent excellent candidates as therapies for attenuating the muscle wasting associated with a number of disease states and ageing. Indeed, acute human studies have observed activation of mTORC1 and its downstream targets (e.g., p70S6K, rpS6, and 4EBP‐1) following ingestion of mixed amino acids, and this is coupled with an increase in muscle protein synthesis (MPS) in the ensuing 60–120 min (Atherton, Etheridge et al, 2010; Koopman et al, 2006; Paddon‐Jones et al, 2004; Volpi, Kobayashi, Sheffield‐Moore, Mittendorfer, & Wolfe, 2003). Furthermore, when human skeletal muscle undergoes loading prior to amino acid ingestion this effect on mTORC1 signaling and MPS is potentiated (Moore, Atherton, Rennie, Tarnopolsky, & Phillips, 2011; Witard et al, 2014).…”
Section: Introductionmentioning
confidence: 99%